Overall Life Satisfaction In Latvia - Čipāne, Kate; Sloka, Biruta (My University, 2019)
The concept of life satisfaction has always been important part of providing well-being of population. Life satisfaction of inhabitants of the country is becoming a greater challenge for country to solve as it affects both personal and professional life of citizens and performances that are made in these fields therefore it is necessary to be aware of the current situation in order to know in what situation Latvia is, what are the challenges and what needs to be improved in the future. The purpose of the study is to analyse overall life satisfaction development in Latvia by gender, age group and education level. The tasks of the study: 1. to analyse different approaches of theoretical findings reflected in scientific publications and previous conducted research results of overall life satisfaction; 2. to investigate existing research findings of overall life satisfaction in the regions in EU and OECD countries; 3. to analyse main factors and problems affecting overall life satisfaction among inhabitants of Latvia. Research methods used in preparation of the paper: scientific publication and previous conducted research results analysis and analysis of Central Statistical Bureau of Latvia conducted survey data on Quality of Life results. Survey results are analysed using indicators of descriptive statistics (indicators of central tendency or location – arithmetic mean, mode, median), indicators of variability (indicators of dispersion – range, standard deviation and standard error of mean), cross-tabulations by age groups, by gender, by education level and by type of household. The results of analysis indicated that Latvia is among the most dissatisfied countries in Europe and for decision makers there are several challenges that need to be overcome.
Keywords: Life satisfaction; Quality of life; Well-being; Research Subject Categories::SOCIAL SCIENCES::Business and economics